SELECTION OF HEAT SUPPLY SOURCE FOR MOBILE BUILDING STRUCTURE - T. I. Dolgikh; S. V. Morozov; Yu. P. Orlov; A. B. Reis; A. Yu Yakovlev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper proposes a vortex heat generator with energy transformation of the highest  state  of matter motion  into  the  lowest  one  as  a  heat  supply  source  for a mobile object. Energy transformation coefficient indices close or equal to 1 have been obtained as a result of experiments on efficiency of the vortex heat generator. Such results can be explained with the help of the 2nd Bohr quantum postulate. Standard series of certified VTG heat generators has been proposed for heat supply of the mobile object (field hospital).